2020
DOI: 10.1049/iet-nbt.2019.0247
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of microRNA‐500a‐3P‐loaded liposomes in the treatment of cisplatin‐induced AKI

Abstract: Cisplatin treatment results in acute kidney injury (AKI) by the phosphorylation of mixed lineage kinase domain-like protein (MLKL). The knockout of MLKL, which is a principle mediator of necroptosis, is believed to alleviate the AKI symptoms. The present study was aimed to improve the therapeutic efficacy in AKI. For this purpose, miR-500a-3P was identified as appropriate miRNA therapeutics and loaded in liposome delivery carrier. The authors have showed that the miR-LIP directly controls the expression of RIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…All studies were published in English, between 2010 and 2021. Most of these studies were conducted in China [24,25,31,32,[36][37][38][39][40][41][42][43][44][47][48][49][50] and the United States of America (USA) [26,27,34,38,46]. The main differences among the 30 included studies were related All studies were published in English, between 2010 and 2021.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All studies were published in English, between 2010 and 2021. Most of these studies were conducted in China [24,25,31,32,[36][37][38][39][40][41][42][43][44][47][48][49][50] and the United States of America (USA) [26,27,34,38,46]. The main differences among the 30 included studies were related All studies were published in English, between 2010 and 2021.…”
Section: Resultsmentioning
confidence: 99%
“…Of the remaining 432 articles, 393 were excluded by reviewing their titles and abstracts. The full text of the remaining 39 articles underwent a review, and 30 studies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ] that met the eligibility criteria were included. Figure 1 shows a flowchart of the literature search and Supplementary Table S1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has been found that miR-449 is highly expressed in CI-AKI, and abnormal expression of miR-449 regulates apoptosis of kidney tubular epithelial cells through deacetylase 1/P53/Bcl2 associated X protein pathway [43]. The synthetic miR-500a-3p liposome could signi cantly reduce kidney injury [44]. The expression of miRNA is regulated in many ways, of which transcriptional regulation is the most common.…”
Section: Discussionmentioning
confidence: 99%
“…Once RIPK1 is activated, its interaction with RIPK3 occurs, forming complex IIb/necrosome, which mediates the phosphorylation of MLKL, whose translocation to the plasma membrane promotes necroptosis by disrupting plasma membrane integrity [ 97 ]. Some studies in renal tubular cells have demonstrated the involvement of miR-500a-3p in RIPK1, RIPK3, and MLKL regulation when these cells are treated with CDDP [ 98 , 99 ]. On the other hand, RIPK1 ubiquitination results in NF-κB activation, mediating the survival and production of multiple inflammatory cytokines, which are also regulated by several miRs when these cells are exposed to CDDP.…”
Section: Involvement Of Non-coding Rnas In Cisplatin Nephrotoxicitymentioning
confidence: 99%